The Effects of Trademark Registration for MSMEs - Balik, Agustina; Tjoanda, Merry; Sopamena, Ronald Fadly (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Trademark rights are exclusive rights granted by the state to trademark owners who are registered for a certain period by using the brand themselves or by giving permission to other parties to use it. Based on Article 3 of Act No. 20 of 2016 Regarding Trademarks and Geographical Indications, it states that trademark rights are obtained after the Brand is registered. Thus, registration is a requirement to obtain legal protection in the field of Trademarks in the field of IPR. The presence of MSMEs in improving the national trade must be supported by the application of laws that function to protect and provide investment guarantees as wide as possible. Purposes of the Research: In the Maluku province, based on data owned by the Maluku Province Cooperatives and MSME Office, many MSMEs have used brands on their business products, but only a few have registered their brands. Factors that influence MSMEs not to register their trademarks are the lack of knowledge and information about the importance of trademark registration. Even though seen from the prospects for MSME businesses in the Maluku province, it is very promising to be able to compete in national and international trade markets.Methods of the Research: The research method used in this study is normative juridical with the nature of the research, namely analytical descriptive. The problem approach used is a statutory and conceptual approach. The analysis of legal materials used is a literature analysis supported by additional data obtained in the field.Results of the Research: Efforts to create IPR-based development strategies is a new challenge for the government to make as a reality. The government's role is very important in spurring and activating MSMEs business actors in managing and implementing marketing strategies that can increase selling power and healthy competitiveness. Registration of trademarks in order to obtain intellectual property rights protection must be a top priority in creating intellectual property-based development. Counseling and outreach regarding the importance of legal registration of marks must be carried out from now on. Not only that, but the process of assisting MSMEs in the registration process must also be carried out, so that the counseling and legal outreach that has been carried out produces results. The advantage that can be obtained by MSMEs if their trademark is registered is the legal protection provided by the state to them, so that there will be no open gaps for other business actors to take advantage of said trademarks.